Wireless Sensor Networks 10th European Conference, EWSN 2013, Ghent, Belgium, February 13-15, 2013. Proceedings - Demeester, Piet.; Moerman, Ingrid; Terzis, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 10th European Conference on Wireless Sensor Networks, EWSN 2013, held in Ghent, Belgium, in February 2013. The 12 revised full papers presented were carefully reviewed and selected from 51 submissions. The papers cover a wide range of topics in the following areas: experimentation and data access; data management; network algorithms and protocols; and physical layer and hardware aspects.
On Assessing the Accuracy of Positioning Systems in Indoor Environments -- TrainSense: A Novel Infrastructure to Support Mobility in Wireless Sensor Networks -- Access Control in Multi-party Wireless Sensor Networks -- HybridStore: An Efficient Data Management System for Hybrid Flash-Based Sensor Devices -- Annotating Real-World Objects Using Semantic Entities -- Data-Aware, Resource-Aware, Lossless Compression for Sensor Networks -- BLITZ: Wireless Link Quality Estimation in the Dark -- Understanding Link Dynamics in Wireless Sensor Networks with Dynamically Steerable Directional Antennas -- On Optimal Connectivity Restoration in Segmented Sensor Networks -- Online Device-Level Energy Accounting for Wireless Sensor Nodes -- Coexistence Aware Clear Channel Assessment: From Theory to Practice on an FPGA SDR Platform -- Battery State-of-Charge Approximation for Energy Harvesting Embedded Systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer system performance; Computer software; Computer Science; Computer Communication Networks; Special Purpose and Application-Based Systems; System Performance and Evaluation; Algorithm Analysis and Problem Complexity